A critical review of trials of transcranial direct current stimulation and trigeminal nerve stimulation for depression: the issue of treatment-emergent mania - Shiozawa,Pedro (2017)
Abstract Objective: This study is a critical review analyzing occurrence of treatment-emergent mania (TEM) related to transcranial direct current stimulation (tDCS) and trigeminal nerve stimulation (TNS). Method: We present a systematic review of the literature on TEM related to tDCS and TNS treatment for major depressive disorder (MDD), conducted in accordance with the recommendations from Cochrane Group and the PRISMA guidelines. Results: Our search identified few reported episodes of TEM in the literature. In fact, we found 11 trials focused on treatment of MDD (seven controlled trials of tDCS and four trials of TNS, three open label and one controlled). We highlight the need for safety assessment in clinical research settings to establish with precision and in larger samples the risks inherent to the technique under investigation. Conclusion: Safety assessment is of fundamental importance in clinical research. TEM is a very important safety issue in MDD trials. Further and larger controlled trials will help to clarify both the safety and the clinical effects of combinations of pharmacotherapy and tDCS or TNS in daily clinical practice.